Direct C–H arylation synthesis of (DD′AD′DA′)-constituted alternating polymers with low bandgaps and their photovoltaic performance1. (2nd June 2015) - Shaker, Mohamed; Trinh, Cuc Kim; Kim, Wonbin; Kim, Heejoo; Lee, Kwanghee; Lee, Jae-Suk
<x xml:space="preserve">Abstract</x> The alternating copolymers possess a planar backbone structure and high intramolecular charge transfer, and they contain a strong push–pull (D–A) system and gave a power conversion efficiency up to 2.36%.